Evaluasi Program Bantuan Sosial Dalam Menurunkan Tingkat Kemiskinan Ekstrem di Daerah Khusus Jakarta ( Studi Di Kampung Apung Jakarta Utara ) - Andrea Mutiara Riyanwar; Bobby Mandala Putra; Budiman Sakti (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2026)
The source of the problem is that social assistance recipients have not received education regarding the funds provided will be used for more priority matters and the fact that some social assistance recipients feel dependent on the assistance provided by the Government. Recipients of social assistance must be given education so that the funds received are not misused by recipients of social assistance. The type of research applied is descriptive research with a qualitative approach with 3 methods of data collection, namely interviews, observation, and documentation. The aim is to determine the Evaluation of Social Assistance Programs in Reducing Extreme Poverty Levels in the Special Region of Jakarta (Study in Kampung Apung North Jakarta). The research aspect that will be studied by the researcher is whether the recipients of social assistance meet the following criteria: 1) Head of family or manager who is not working. 2) Worried about not being able to eat. 3) Daily food expenses. 4) new clothes in the last year. 5) Floor of a residential building. 6) Walls of the residence. 7) Toilet facilities. 8) Lighting in the house.